2009
DOI: 10.1111/j.1751-9004.2009.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Most Important Dimensions of Personality?Evidence from Studies of Descriptors in Diverse Languages

Abstract: Progress is reviewed with respect on how attributes of personality and character can best be organized and structured. Key insights on this important scientific issue have been gained by a lexical approach, which posits that the degree of representation of an attribute in language corresponds substantially with the general importance of the attribute in real‐world transactions. The rationale for studying the language of personality is explained, followed by a review of the most salient findings from lexical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 66 publications
2
48
0
1
Order By: Relevance
“…They found that people universally cherish a communal value orientation more than they cherish an agentic value orientation, and values are widely regarded as the “conceptual tools and weapons that we all employ in order to maintain and enhance self‐esteem” (Rokeach, , p. 14). Second, Extraversion and Openness are core elements of agency, whereas Agreeableness and Conscientiousness are core elements of communion (Paulhus & John, ; Saucier, ), and Neuroticism and self‐esteem share a genetic core (Neiss, Stevenson, Legrand, Iacono, & Sedikides, ) or “may be markers of the same higher order concept” (Judge et al., , p. 693). Therefore, it is informative to find out whether low Neuroticism (proxy for self‐esteem) is more strongly tied to Extraversion‐Openness (proxy for agency) or to Agreeableness‐Conscientiousness (proxy for communion).…”
Section: The Importance Of Understanding Sources Of Self‐esteemmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that people universally cherish a communal value orientation more than they cherish an agentic value orientation, and values are widely regarded as the “conceptual tools and weapons that we all employ in order to maintain and enhance self‐esteem” (Rokeach, , p. 14). Second, Extraversion and Openness are core elements of agency, whereas Agreeableness and Conscientiousness are core elements of communion (Paulhus & John, ; Saucier, ), and Neuroticism and self‐esteem share a genetic core (Neiss, Stevenson, Legrand, Iacono, & Sedikides, ) or “may be markers of the same higher order concept” (Judge et al., , p. 693). Therefore, it is informative to find out whether low Neuroticism (proxy for self‐esteem) is more strongly tied to Extraversion‐Openness (proxy for agency) or to Agreeableness‐Conscientiousness (proxy for communion).…”
Section: The Importance Of Understanding Sources Of Self‐esteemmentioning
confidence: 99%
“…Second, Robins, Tracy, Trzesniewski, Potter, and Gosling () examined the relation between the Big Five and self‐esteem in a sample of over 300,000 participants. Both Extraversion‐Openness (i.e., agentic aspects) and Agreeableness‐Conscientiousness (i.e., communal aspects; Saucier, ) were, on average, moderately related to self‐esteem. Schmitt and Allik () reported similar relations at the country level.…”
Section: The Importance Of Understanding Sources Of Self‐esteemmentioning
confidence: 99%
“…Reviews (e.g.. Saucier, 2009b;Saucier & Goldberg, 2001) indicate that previous lexical studies of personality-to varying degrees, including other human-attribute terms-have provided evidence to support more than one structural model. These structural models vary principally in how many dimensions they contain.…”
Section: Studymentioning
confidence: 99%
“…This view is in agreement with several recent studies on personality (cf., Ashton and Lee, 2005; Saucier, 2009; De Raad et al, 2010). …”
Section: Introductionmentioning
confidence: 99%